Вміст фібронектину у сироватці крові хворих на цукровий діабет 2-го типу та ожиріння - Могильницька, Л. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
Macro- and microvascular disease is the main cause of disability and death in diabetes. Endothelial dysfunction is considered an early and important step in the development of arterial disease. Circulating cellular fibronectin may be another useful marker of endothelial activation. The aim of study was to investigate serum level of fibronectin in patients with type 2 diabetes with different body mass and obesity. We found an increase of serum level of fibronectin in obese and non-obese diabetic patients and non-diabetic patients with obesity. Revealed changes may be a marker of endothelial dysfunction in diabetes and obesity.